2017
DOI: 10.1111/jace.15272
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for the composition dependence of glassy dynamics

Abstract: The problem of glass relaxation is traditionally known as one of the most challenging problems in condensed matter physics, with important implications for several high‐tech applications of glass. In this study, we present a predictive model for the temperature, thermal history, and composition dependence of glassy relaxation dynamics. Our model enables, for the first time, the quantitative prediction of relaxation behavior for new glass compositions. Using the commercial Corning EAGLE XG® alkaline earth alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
(110 reference statements)
0
16
0
Order By: Relevance
“…The missing model required to understand structural relaxation is the bulk viscosity curve 15 . All previous relaxation (structural or stress) models 9,42 have relied on approximations that use a constant exponent β and on a constant (temperature‐independent) modulus value, whereas here, every parameter of Equation () may be modeled as a function of temperature. Furthermore, in combination with the relaxation models described by Guo et al, 42 in which multiple fictive temperatures are described using a Prony series and a temperature‐dependent modulus, one can construct a relaxation curve accounting for the temperature dependence and thermal history dependence of all relevant parameters:exp)(G(T)tη(T,Tnormalf)βTffalse∑i=1Nwi)(Tnormalfexp)(G(T)ki)(Tnormalftηfalse(T,Tffalse).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The missing model required to understand structural relaxation is the bulk viscosity curve 15 . All previous relaxation (structural or stress) models 9,42 have relied on approximations that use a constant exponent β and on a constant (temperature‐independent) modulus value, whereas here, every parameter of Equation () may be modeled as a function of temperature. Furthermore, in combination with the relaxation models described by Guo et al, 42 in which multiple fictive temperatures are described using a Prony series and a temperature‐dependent modulus, one can construct a relaxation curve accounting for the temperature dependence and thermal history dependence of all relevant parameters:exp)(G(T)tη(T,Tnormalf)βTffalse∑i=1Nwi)(Tnormalfexp)(G(T)ki)(Tnormalftηfalse(T,Tffalse).…”
Section: Discussionmentioning
confidence: 99%
“…The composition‐dependent part of Equation () is S since we approximate A to be independent of composition. The fragility dependence of S was proposed by Guo et al, 42 Sfalse(xfalse)=Sfalse(xreffalse)expm(x)m(xref)m0,where x is composition and x ref is a reference composition in the same glass family. Seeking the simplest possible expression to approximate the unknown ζ , we take the natural logarithm of Equation () and of Equation () and combine them to getlnζ=mm0+lnζ,with the additional definitionlnζ=lnπS)(xref6)(ln10A1false/2mxrefm0.…”
Section: Modelmentioning
confidence: 99%
“…[66]. The MAP model is also able to predict the composition dependence of (T,Tf) based on the underlying topology of the glass network in terms of temperature-dependent constraint theory [67]- [70]. The detailed form of the MAP model is provided in Ref.…”
Section: Modeling Of Glass Relaxationmentioning
confidence: 99%
“…The detailed form of the MAP model is provided in Ref. [70]. However, please note that the analysis of the Prony series presented in the current paper does not depend upon the particular choice of model for (T,Tf).…”
Section: Modeling Of Glass Relaxationmentioning
confidence: 99%
“…Sub-T g glass relaxation -also called aging -has been extensively studied over the years [22][23][24][25][26][27][28][29][30][31][32][33][34] and it has been shown that the relaxation process depends on multiple factors including the nonexponentiality β, the non-linearity x, the fictive temperature T f and the fragility index m. The fragility is of particular interest as it affects the relaxation process in multiple ways that may appear contradictory. For example glasses located within the "reversibility window" are generally found to correspond to compositions exhibiting lower fragility index 35 so that prior suggestions that these glasses do not age, may appear to indicate that low fragility is associated with a resistance to relaxation.…”
Section: Introductionmentioning
confidence: 99%